Detection of MicroRNAs in Extracellular Vesicles Secreted by Umbilical Cord-derived Mesenchymal Stem Cells - Huyen, Nguyen Thu; Chau, Duong Minh; Phuong, Do Thi Xuan; Liem, Nguyen Thanh; Uyen, Than Thi Trang (VNU Journal of Science: Natural Sciences and Technology, 2021)
Extracellular vesicles (EVs) are emerging as a potential candidate for disease treatment due to their bioactive cargoes. Recently, mesenchymal stem cells (MSC)-derived EVs have shown their capacity to replace parental cells as their similar functions to MSCs. The therapeutic effects of EVs depend on their cargo, such as DNA, miRNA, proteins, and lipids. In this study, we expanded umbilical cord-derived MSCs (UCMSCs) for EV release. Additionally, we evaluated the expression level of several microRNAs in three EV populations, including apoptotic bodies (AB), microvesicles (MV), and exosomes (EX). Results showed that UCMSCs released three EV types: AB, MV, and EX into culture media. The three EV populations were different in morphology and size. Three EVs were detected to carry microRNAs, such as hsa-miR-320, hsa-miR-181b, and hsa-miR-140. Among these microRNAs, hsa-miR-140 expressed with the greatest level, followed by hsa-miR-181b and hsa-miR-320. The results of this study provide more knowledge about UCMSC-derived EV miRNAs in addition to reveal the potential role of UCMSC-EVs associated with detected miRNAs.